Traditions of Analysis and Synthesis
VII, 402 p. 26 illus., 4 illus. in color.
Keywords: This open access book provides a fresh perspective on analysis and synthesis across several areas of inquiry. The two operations form a primary basis of modern laboratory science, ranging from the spectrographic analysis used in practically every scientific discipline today, to the naming of entire disciplines, such as synthetic organic chemistry. Despite their acknowledged significance, however, the history of analysis, synthesis, and their relations over the longue durée is poorly understood. Several volumes have been devoted to the history of analysis and synthesis in the sense that premodern mathematicians and philosophers used the terms, but very little work has been done on the tradition of material decomposition and recomposition and its relationship to mathematics and philosophy. The present volume brings together scholars in the history of medicine, mathematics, philosophy, chemistry, and alchemy to explore the ways in which these multiple disciplines understood and used analysis and synthesis as experimental, justificatory, and conceptual tools.